2017
DOI: 10.1007/s11523-017-0520-7
|View full text |Cite
|
Sign up to set email alerts
|

Non-Small-Cell Lung Cancer (NSCLC) Harboring ALK Translocations: Clinical Characteristics and Management in a Real-Life Setting: a French Retrospective Analysis (GFPC 02–14 Study)

Abstract: The results of this real-life analysis suggest that the prognosis of NSCLC patients with theALK translocation may be better than that of the overall NSCLC population, but the outcomes were poorer than those of ALK+ NSCLC patients included in clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…To the best of our knowledge, it is the largest retrospective analysis, including the highest number of ALK+ NSCLC patients. [11][12][13] To summarize the role of radiological imaging methods in diagnosis and differential diagnosis of patients with ALK+ NSCLC, about 44.1% of patients had centrally, and 55.9% had peripherally localized lesions. In addition, cavitation was reported in only 7.7%, while effusion was present in about one-third of cases; 25.1% of the patients had brain metastasis and the median PFS was 14 months.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, it is the largest retrospective analysis, including the highest number of ALK+ NSCLC patients. [11][12][13] To summarize the role of radiological imaging methods in diagnosis and differential diagnosis of patients with ALK+ NSCLC, about 44.1% of patients had centrally, and 55.9% had peripherally localized lesions. In addition, cavitation was reported in only 7.7%, while effusion was present in about one-third of cases; 25.1% of the patients had brain metastasis and the median PFS was 14 months.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed that a subset of patients had an extremely poor response to crizotinib (PFS <3 months) with poor survival (no longer than 6 months) compared with the literature. [2][3][4][5][6] Although they did not receive subsequent next-generation TKIs, their survival rate was worse than patients who only received crizotinib followed by chemotherapy, with a median survival of 20 months. 3 In the ALEX study, among patients who received crizotinib and alectinib, patients with early resistance to TKI had shorter survival (no longer than 12 months).…”
Section: Discussionmentioning
confidence: 99%
“…Anaplastic lymphoma kinase ( ALK )‑fusion genes represent a small but important part of oncogenic driver mutations in NSCLC, accounting for approximately 3%‑7% of all cases worldwide. 1 , 2 Small molecule tyrosine kinase inhibitors (TKIs) are the standard therapy for ALK -rearranged NSCLC. Crizotinib, a first-generation TKI, is the most widely used targeted drug to treat ALK -rearranged NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Approximately 3% to 5% of cases of NSCLC are histologically defined as anaplastic lymphoma kinase (ALK) positive (ALK1). 1,4,5 ALK1 NSCLCs are associated with advanced clinical stage at presentation and are more frequently observed in nonsmokers and younger patients compared with ALK-negative disease. 6 The current standard first-line treatment for patients with advanced ALK1 NSCLC is a firstor second-generation ALKtyrosine kinase inhibitor (TKI); nevertheless, many patients develop resistance to their initial and subsequent ALK-TKIs.…”
Section: Introductionmentioning
confidence: 99%